Defragmenting really speeds up Windows NT machines. - Robb, D. (IEEE spectrum)
When they want to improve the operation of a PC running the Windows NT operating system, most people think of adding RAM or upgrading to a more powerful processor. Research proves there is a simpler solution: every so often, reorder the disk contents so that every file is stored in one piece, butted up against the next file. Files these days are usually fragmented and the fragments scattered all over the disk. When they are not, the disk drive's read/write head has less distance to travel and the left-over free space, being all in one place, will accept a larger chunk of file data. This defragmentation can more than triple system responsiveness, according to a study by the independent software testing laboratory NSTL Inc., Conshohocken, Pa. Just by running software that organizes a disk's contents properly both individuals and corporations can enjoy faster system performance